Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1097/dbp.0b013e318196b0de
|View full text |Cite
|
Sign up to set email alerts
|

Acute Posttraumatic Stress Symptoms Among Urban Mothers With Newborns in the Neonatal Intensive Care Unit: A Preliminary Study

Abstract: Addressing acute posttraumatic stress symptoms may enhance interventions to help urban families of NICU infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
75
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 33 publications
6
75
1
2
Order By: Relevance
“…[1][2][3] This nonnormative transition to parenthood has been described as an "emotional crisis" 4 that typically is characterized by feelings of loss and grief, [5][6][7] which sometimes persist for months after the infant's NICU discharge. 1,[8][9][10][11] In some ways, adaptation to having a preterm infant is similar to adaptation to having a child with a disability; the mother must adjust her expectations and hopes for her child in the face of uncertainties, and she must mourn the hoped-for child while still embracing the child she has.…”
mentioning
confidence: 99%
“…[1][2][3] This nonnormative transition to parenthood has been described as an "emotional crisis" 4 that typically is characterized by feelings of loss and grief, [5][6][7] which sometimes persist for months after the infant's NICU discharge. 1,[8][9][10][11] In some ways, adaptation to having a preterm infant is similar to adaptation to having a child with a disability; the mother must adjust her expectations and hopes for her child in the face of uncertainties, and she must mourn the hoped-for child while still embracing the child she has.…”
mentioning
confidence: 99%
“…1,2 The complex reactions of these parents include feelings of guilt, sadness over the loss of the "perfect" child, depression, and posttraumatic stress disorder (PTSD). 1,[3][4][5] Vanderbilt et al 6 found that 23% of NICU mothers met criteria for acute stress disorder (ASD) while Pierrehumbert et al 7 documented the presence of symptoms of PTSD in 41% of NICU parents up to 14 months after their infant' s birth. Data also suggest that up to 83% of mothers who experience significant trauma also endorse distorted views of their infants.…”
mentioning
confidence: 99%
“…2 In addition to high rates of depression, [3][4][5] researchers have identified acute stress disorder (ASD) and posttraumatic stress disorder (PTSD) as features of parental psychological reactions. [6][7][8][9][10][11][12] To date, interventions developed to reduce psychological distress in parents of preterm infants have been primarily supportive or educational in nature. [13][14][15] More recently, a small number of studies have evaluated intervention programs focused on reducing parental stress 16 and trauma symptoms.…”
mentioning
confidence: 99%